2022
DOI: 10.1038/s41598-022-09109-9
|View full text |Cite
|
Sign up to set email alerts
|

Saffron extract and crocin exert anti-inflammatory and anti-oxidative effects in a repetitive mild traumatic brain injury mouse model

Abstract: Saffron Crocus sativus L. (C. sativus) is a flower from the iridaceous family. Crocin, saffron’s major constituent, and saffron have anti-oxidative and anti-inflammatory activities. In this work, the neuroprotective effects of saffron and crocin are being investigated in a repetitive mild traumatic brain injury (rmTBI) mouse model. A weight drop model setup was employed to induce mild brain injury in male albino BABL/c mice weighing 30–40 g. Saffron (50 mg/kg) and crocin (30 mg/kg) were administrated intraperi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 82 publications
2
26
0
1
Order By: Relevance
“…Intraperitoneal treatment with saffron stigma extract or petal extract was associated with an LD50 value of 1.6 g/kg and 6 g/kg, respectively [ 26 , 160 , 175 , 176 , 177 ]. The LD50 of CRCs is estimated at >3 g/kg [ 26 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intraperitoneal treatment with saffron stigma extract or petal extract was associated with an LD50 value of 1.6 g/kg and 6 g/kg, respectively [ 26 , 160 , 175 , 176 , 177 ]. The LD50 of CRCs is estimated at >3 g/kg [ 26 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Saffron and its metabolites did not cause any significant hematological or biochemical toxic effects, nor were associated with histotoxicity in heart, liver, spleen and kidney, or genotoxic and mutagenic effects [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. CRCs in preclinical mice models were well tolerated in doses up to 3 g/kg, in intraperitoneal or oral administration for acute exposure and 400 mg/kg in intraperitoneal administration for subacute exposure (3–4 weeks) [ 26 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both aqueous and ethanolic saffron extracts were shown to exert anti-inflammatory effects in induced chronic inflammation in mice [ 61 ]. A recent study in a repetitive mild non-invasive traumatic brain injury mouse model showed that saffron extract and crocin suppress TBI-induced inflammatory and oxidative responses by decreasing the levels of IFN-γ, TNF-α, MPO, GSH, and MDA [ 31 ]. Furthermore, dysregulation in both excitatory and inhibitory neurotransmission has been shown after TBI [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that saffron has a broad spectrum of pharmacological properties, including anti-hyperglycemic [ 28 ], anti-depressive [ 29 ], anti-tumor [ 27 ], and anti-oxidant [ 30 ] effects that have been identified in rodent disease models. Specifically, administration of crocin in a controlled cortical impact (CCI) model of TBI in mice showed a decrease in brain edema and neurological motor severity score [ 31 ]. Apoptotic cell death and neuroinflammation were inhibited in a TBI-induced mouse model treated with crocin, through the Notch signaling pathway [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Modern pharmacological studies of saffron and its main constituents have revealed a wide spectrum of biological activities (i.e., anti-inflammatory, antinociceptive, antioxidant, immunoregulatory effects, neurodegenerative diseases, cardiovascular diseases, anticancer, anti-arthritic effects and protection against natural and chemical toxins) ( Attia et al, 2021 ; Xing et al, 2021 ). Crocin, mono, and diglycosyl esters of a polyene dicarboxylic acid are some of the main active components that are responsible for the pharmacological effects of saffron ( Abdi et al, 2022 ; Salem et al, 2022 ; Xu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%